تنفيذ تعليم مهارة الكلام لتنمية البيئة الاصطناعية في إندونيسيا دراسة الحالة في معهد الإصلاح بجيغاواه مدينة جمبر جاوى الشرقية - Muhammad Ainul Yaqin; Ecky Cahyo Pratama; Achmad Ja'far Sodik (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2021)
The ability to make all students able to practice speaking Arabic in everyday life is not easy to apply to every particular institute or educational institution. Because it requires an intensive and patient process. The Institute of Reform is a boy's institute but is competitive and proven. The purpose of this research is: 1. To learn the implementation of speech skill education. 2. Detecting the factors supporting speech skills at the Institute of Reform in Jigwah. 3. Detection of inhibiting factors to learn the skill of speech at the Institute of Reform in Jigwah.This research used the qualitative input, the descriptive approach, which was signed at the Institute of Reform in Jigwah. The way to identify the search detective is in the "purposive sampling" way. Data collection method:1. Note 2. Interview 3. Documents. The researcher uses data analysis on three identical activities, including data classification, data presentation and summary. The results of this research are: implementation of speech skill education at the Institute of Reform in improving the quality of speech skill for students of the Reform Institute has several stages: 1. Vocabulary Preservation, 2. Speech Application, 3. Understand the rules. Supporting factors that support the successful implementation of speech skill education at the Institute of Reform in the formation of students who are experts in the practice of speech skill, among other things. Compulsory Arabic System, B. Professional Teacher, J. Morning Grammar Method, D. Effective and Appropriate Environment.3 Inhibition factors hinder the successful implementation of speech skill education at the Institute of Reform in the Formation of Students who are experts in the practice of speech skill, among other things: A. Learner Aand, B. Selfish teacher, c. influence of regional languages.